Byles on bills of exchange : the law of bills of exchange, promissory notes, bank notes and cheques - Megrah, Maurice; Ryder, F. R; Byles, John Barnard (London : Sweet and Maxwell, 1972)
In previous editions certain sections of the parent statue were not given in full, where the reminder was not especially relevant in the particular context, they are today repeated. This edition has accordingly been rearranged, without altering its characteristic treatment.
First ed. published in 1829 under title: Law of bills of exchange, promissory notes, bank-notes, bankers' cash-notes, and checks.
Includes index
ucj, 15/01/2019
Loans
Keywords: Negotiable instruments